Relationship between timing of the first zygotic cleavage with cytoskeletal structures and amino acid metabolic profiles in vitrified mouse embryos / Wan Hafizah W. Jusof - W. Jusof, Wan Hafizah (Institute of Graduate Studies, UiTM, 2017)
Timing of the first zygotic cleavage has been used as a marker of embryo developmental competence and subsequent viability. Previous studies showed that embryos that cleaved early had higher developmental viability. However, the factors contributing to timing of the first zygotic cleavage are unknown. Energy production from mitochondria, nucleus and cytoskeletal organization might be some of the factors involved. Amino acid metabolic profiles might also relate with timing of the first zygotic cleavage as it has been reported to have significant relationships with embryo viability. Thus, the present study was designed to investigate the relationship between timing of the first zygotic cleavage, amino acid metabolic profiles, mitochondria, nucleus and cytoskeletal organization of mouse embryos with subsequent viability. Embryos were retrieved from superovulated ICR mice, 28 hours after hCG injection. At this point of time, 2-cell stage embryos were categorized as early-cleaving (EC), while zygotes with two pronuclei as late-cleaving (LC) embryos. Embryos were cultured overnight in M16 medium supplemented with 3% Bovine Serum Albumin (BSA) in a humidified carbon dioxide (CO2) incubator. For Experiment 1, both EC and LC embryos were divided into control and treatment groups. For control group, 2-cell stage embryos were cultured until the blastocyst stage. For treatment group, embryos were vitrified by EFS40 or EFS20/40 method for 1 hour and warmed. The vitrifiedwarmed embryos were cultured until the blastocyst stage. The number of surviving embryos and their development to the blastocyst were observed and counted…